102 A system for improved burn injury surveillance in resource-limited settings. (1st September 2016) - Sugerman, David; Falk, Henry; Meddings, David; Mehta, Sumi; Peck, Michael; Sage, Michael
Abstract : Background: There are limited and fragmented data collection systems for burn injury. A global repository may lead to better burn injury estimates and help identify key risk factors. A collaborative effort involving the World Health Organisation (WHO), the Global Alliance for Clean Cookstoves, the U.S. Centres for Disease Control and Prevention (CDC), and the International Society for Burn Injuries was undertaken to simplify and standardise in-patient burn data collection. Utilising an expert panel of epidemiologists and burn care practitioners, a new form and online data entry system was developed which can be used in resource-abundant or resource-limited settings. The Global Burn Registry (GBR) form has three functions: 1) to determine the magnitude and risk factors for burns, 2) provide baseline and follow up data to test primary prevention interventions, and 3) be designed for use without modification around the world. Methods: After development, international burn organisations, CDC and WHO solicited burn centre participation to pilot test the GBR system. WHO and CDC led a webinar to describe system implementation. Results: During an 8 month period, 55 hospitals in 29 countries enrolled in the pilot and were provided the GBR instrument, guidance, and data visualisation tool. Evaluations were received from 29 hospitals (53%). Key findings were: median time to upload completed forms was less than 10 minutes; physicians most commonly entered data (64%), followed by nurses (25%); layout, clarity, accuracy, and relevance were all rated high; and a vast majority (85%) considered the GBR "highly valuable" for prioritising, developing, and monitoring burn prevention programs. Conclusions: The GBR was shown to be simple, flexible, and acceptable to users. Enhanced regional and global understanding of burn epidemiology may help prioritise the selection, development, and testing of primary prevention interventions for burns in resource-limited settings.